2012
DOI: 10.1111/j.1442-200x.2012.03693.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for treatment outcomes in transient tachypnea of the newborn

Abstract: Late-preterm delivery, lower initial umbilical artery pH (<7.25), and lower Apgar score at 1 min were independently associated with poor prognostic treatment outcomes in infants with TTN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 18 publications
(19 reference statements)
0
19
0
Order By: Relevance
“…The risk factors associated with TTN includes; prematurity, male sex, large birth weight, meconium-stained amniotic fluid, cesarian section delivery(esp. elective cesarean), gestational diabetes, maternal chorioamnionitis and maternal asthma (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…The risk factors associated with TTN includes; prematurity, male sex, large birth weight, meconium-stained amniotic fluid, cesarian section delivery(esp. elective cesarean), gestational diabetes, maternal chorioamnionitis and maternal asthma (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…TTN is generally a benign disease and treated with a brief course of oxygen. However, some of the cases need invasive or non-invasive respiratory support 6,7,11,12 .…”
mentioning
confidence: 99%
“…Previous studies have reported that lower Apgar scores, male sex, late-preterm delivery, maternal diabetes, and cesarean delivery were related to poor prognoses in infants with TTN [18][19][20]. Aydemir et al [21] reported that measurements of NT-proBNP are valuable for evaluating the prognosis of lung disease and can also identify infants at risk of prolonged tachypnea and respiratory support requirement.…”
Section: Discussionmentioning
confidence: 97%